1996
DOI: 10.1126/science.273.5272.228
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Suppression of Cell-Mediated Immunity by Measles Virus

Abstract: The mechanisms underlying the profound suppression of cell-mediated immunity (CMI) accompanying measles are unclear. Interleukin-12 (IL-12), derived principally from monocytes and macrophages, is critical for the generation of CMI. Measles virus (MV) infection of primary human monocytes specifically down-regulated IL-12 production. Cross-linking of CD46, a complement regulatory protein that is the cellular receptor for MV, with antibody or with the complement activation product C3b similarly inhibited monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
333
2
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 522 publications
(352 citation statements)
references
References 49 publications
15
333
2
2
Order By: Relevance
“…A role of CD46 in IL-12p40 and p70 expression have been previously reported (Karp et al, 1996;KuritaTaniguchi et al, 2000;Schnorr et al, 1997;Smith et al, 2003). Hence, we analyzed the role of CD46 in both IL-12 and IL-23 inductions.…”
Section: Cd46 Modulates Lps-mediated Maturation Of Mdcsmentioning
confidence: 78%
See 2 more Smart Citations
“…A role of CD46 in IL-12p40 and p70 expression have been previously reported (Karp et al, 1996;KuritaTaniguchi et al, 2000;Schnorr et al, 1997;Smith et al, 2003). Hence, we analyzed the role of CD46 in both IL-12 and IL-23 inductions.…”
Section: Cd46 Modulates Lps-mediated Maturation Of Mdcsmentioning
confidence: 78%
“…Production of IL-12p70 by APC can be modulated by cross-linking of CD46 at their surface, either increasing or decreasing IL-12 depending on the cell type and stimulus used. An inhibition of IL-12 production by monocytes is observed after CD46 ligation by antibodies or C3b binding (Karp et al, 1996), and a posttranscriptional inhibition of IL-12p70 was also observed when CD46 was triggered by HHV6 (Smith et al, 2003). On the other hand, IL-12p40 was increased by CD46 ligation on GM-CSF treated monocytes (KuritaTaniguchi et al, 2000), and infection of dendritic cells by measles virus led to an increase in IL-12p40 (Schnorr et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that IL-12 is important to the development of cell-mediated immunity and is a necessary cytokine for acquisition of a Th1 type immune response [17,35]. It was demonstrated that measles virus binding to the CD46 receptor leads to down-regulation of IL-12 secretion in measles-infected monocytes after in vitro measles stimulation [16,21]. The decrease in IL-12 production by monocytes was shown to be greater when the p40 monomer was measured rather than the bioactive p70 heterodimer [16,41].…”
Section: Discussionmentioning
confidence: 99%
“…Two main T helper subsets have been recognized: Th1 cells producing cytokines favoring cell-mediated immunity (IFN-γ, IL-2, TNF-α and IL-12), and Th2 cells producing cytokines necessary for humoral immune responses (IL-4, IL-5, IL-6, IL-10, and IL-13) [13,14]. Measles virus infection induces a Th2 type response and it is likely that cytokine imbalances play a role in immunosuppression [15][16][17][18]. In contrast, vaccination with measles virus preferentially induces Th1 type immune responses [19][20][21].…”
Section: Introductionmentioning
confidence: 99%